Measuring cultural competence in emergency management and homeland security higher education programs. (2nd October 2018) - Haupt, Brittany; Connolly Knox, Claire
ABSTRACT: With the evolving demographics of our communities and recent disasters directly impacting socially vulnerable populations, cultural competency has increased in importance. Emergency management and homeland security scholars have outlined various interpersonal and technical knowledge, skills, and abilities for the discipline; yet lacking in this discussion is cultural competency. By increasing cultural competency knowledge, skills, and abilities in emergency management higher education, we increase our graduates to be more credible, empathetic, relatable, and trustworthy, and less inclined to negatively apply biases, stereotypes, and pre-conceived notions. Using results of a national survey to U.S. Emergency Management and Homeland Security Higher Education programs, we apply Cross' cultural competence continuum to provide a contextual landscape of the inclusion of these knowledge, skills, and abilities in related courses within the curriculum. We conclude with lessons learned and recommendations for program directors who want to move forward on the continuum.